Plan de marketing para la comercialización de hortalizas orgánicas de los grupos frutos y raíces del Centro Experimental La Playita en el cantón La Maná provincia de Cotopaxi año 2012-2016 - Lasluisa Esmeraldas, Mayra Mercedes (2015)
This investigation aims to design a marketing plan for organic vegetables commercialization in La Maná cantón, Cotopaxi province in the years 2012 -2016 for which the theory of the 4 P’s was addressed relative to the vegetables commercialization. The descriptive, exploratory, correlational and explanatory investigation were applied, the surveys were applied to the consumers and the consumption of vegetables in the families of this canton was analyzed, observing that the organic vegetables have a good acceptance in the local market, some aspects for the commercialization were determined such as: the packing and the label of the vegetables, it generated an IRR of 13,18%, and a NPV of 7.748,47; and a cost benefit of 0,38 that gives like a result that this marketing plan is profitable and feasible.